The multiprofessional team front of the patient suffering from cardiorespiratory arrest (Research, Society and Development, 2020)
Cardiorespiratory arrest (CRP) consists of a sudden interruption of circulation and breathing, characterized as an emergency requiring a team qualified to act in an agile manner, to minimize risks and ensure patient survival. The objective of this study was to carry out a bibliographic survey about the multiprofessional team in the face of the patient victim of cardiorespiratory arrest. It is a descriptive study, of the type integrative literature review, of a qualitative character, the search occurred in the databases: LILACS, SCIELO and BDENF, via VHL, and Scholar Google. The articles were collected in the period of September 2020. The descriptors were used: Patient assistance team, Cardiorespiratory arrest and Urgency, located in the list of Health Sciences Descriptors (DECs). After applying the eligibility criteria, 8 studies remained. The multiprofessional team in front of the patient suffering from cardiopulmonary arrest must be qualified, work in an integrated manner, ensuring quality care aimed at the patient's recovery. It was concluded that the multiprofessional team, acting together and in a synchronized manner, improves the patient's health condition, increasing the patient's survival and reducing the sequelae that can be generated by PCR.